Pelatihan Lean Hospital di Rumah Sakit Gotong Royong Surabaya: Lean Hospital Training at Gotong Royong Hospital Surabaya - Dewi, Dian Retno Sari; Karijadi, Irene; Gunawan, Ivan; Wibowo, Wahyudi; Mulyana, Ig. Jaka; Hermanto, Yustinus Budi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Hospitals should improve services to patients. The concept of Lean Management can be used as an approach to improve hospital efficiency. The purpose of the training is to provide an understanding of Lean Management in hospitals (Lean Hospital) to hospital leaders and employees and be able to identify waste. The training was conducted with partners, namely Surabaya Gotong Royong Hospital. The training methods are the presentation of Lean Hospital and group discussions. Through this training, the knowledge of leaders and employees of Gotong Royong Surabaya Hospital about Lean Hospital can be improved. In group discussions, various types of waste and the order of priority for improvement were identified. This training has been able to increase the understanding of leaders and employees of Gotong Royong Surabaya Hospital about Lean Hospital. This can be seen from the ability of participants in the discussion to identify and assess the priority number of waste and provide suggestions for improvement. This activity can be followed up with research or community service on improving efficiency at Gotong Royong Surabaya Hospital with the Lean Management approach.